Pengaruh Gaya Kepemimpinan dan Disiplin Kerja Terhadap Kinerja Karyawan pada PT Mega Niaga Sejahtera - Sintia Rahayu Mardyaningrum; Melisa Zuriani Hasibuan (JURNAL RISET MANAJEMEN (JURMA), 2024)
This study aims to analyze the influence of leadership style and work discipline on employee performance at PT Mega Niaga Sejahtera. The research design uses a quantitative descriptive approach with an ordinal scale, where the respondents were taken using a simple purposive sampling method of 50 people through distributed questionnaires. Data analysis used consisted of instrument testing, classical assumption testing, multiple linear regression analysis, and hypothesis testing. Data were processed using SPSS 24.0 for Windows. The results of the study prove that leadership style and work discipline simultaneously or together have a positive and significant effect on employee performance at PT Mega Niaga Sejahtera. The t-value of leadership style is 1.122> 1.676 with a significance level of 0.268> 0.05, the t-value of work discipline is 12.490> 1.676 where the significance level is 0.000 <0.05 so that it means that X1 is not accepted, while X2 is accepted in influencing employee performance at PT Mega Niaga Sejahtera. The results of the determination coefficient (R2) indicate that leadership style and work discipline have an effect on employee performance of 77.2% and the remaining 22.8% of employee performance is influenced by other factors not examined in this study.